Estudo anatômico do haustório da erva-de-passarinho (Struthanthus marginatus (desr.) blume), em diversas plantas, em Viçosa - Shimoya, Chotaro; J Gomide, Carlos (Revista Ceres, 2025)
The development of hautoria of de plant parasite (Struthanthus marginatus (Desr. ) Blume) is described for tenplants studied. The phenomena of scarring in orange tree is studied, also.